The Role of Nature in Arctic Tourist Motivations and Arctic Tourist Attractions - Anderson, Andrea (2015)
Tourism is an important economic activity and, in many rural areas, it is replacing traditional industries to become the most important industry. This is particularly true in Arctic areas where an increase in visitors means a focus has to be placed on understanding this growing industry. Arctic environments are usually delicate so an increase in tourist numbers can have a significant impact if it is not controlled or managed properly. Tourists have expectations when they visit a destination and companies that provide activities must be able to provide activities which tourists are interested in in order to continue to operate. The purpose of this study is to explore Arctic tourism, with a particular focus on Tromsø and northern Norway. Using qualitative interviews, with both tourists who have visited the Arctic and people working in the tourist industry in Tromsø, the study aims to explore why tourists choose to visit the Arctic and the role of nature in tourism. The Scandinavian concept of friluftsliv is examined for its relevance to tourist activities and how it may play a role in shaping the industry due to its position as a Scandinavian nature construct. By examining what tourists wish to experience and what companies offer, as well as why they offer certain activities, it is possible to build a bigger picture of the industry in Tromsø and northern Norway.